Effect of process mode, nitrogen source and temperature on L-malic acid production with Aspergillus oryzae DSM 1863 using acetate as carbon source - Kövilein, Aline; Zadravec, Lena; Hohmann, Silja; Umpfenbach, Julia; Ochsenreither, Katrin (Frontiers in Bioengineering and Biotechnology, 2022)
Malic acid, mainly used as acidulant and taste enhancer in the food industry, is currently produced from fossil resources. In this study, microbial L-malate production with the filamentous fungus Aspergillus oryzae using the carbon source acetate was evaluated. Acetate is for example contained in biomass-derived substrates such as lignocellulosic hydrolysates and condensates of fast pyrolysis, thus avoiding competition with food production. Since research on malic acid synthesis from acetate is limited and reported productivities and yields are low, this work aimed to improve the process. First, different cultivation temperatures were tested. This parameter was found to affect the ratio between malic and succinic acid, which is the major by-product of organic acid production with A. oryzae. At 32 °C, the malate share was highest (53.7 ± 1.6 %), while it was lowest at 38 °C (43.3 ± 1.1 %) whereas succinate represented the main product (51.5 ± 1.0 %). Besides the temperature, the type of nitrogen source was also found to affect malate synthesis as well as biomass production. In the pre-culture, the biomass concentration was increased by a factor of 3.4-3.9, and germination started earlier with the complex nitrogen sources yeast extract, casein hydrolysate and peptone compared to the defined nitrogen source (NH4)2SO4. Especially with yeast extract, malate synthesis in the main culture was accelerated and the titer obtained after 48 h was about 2.6 times higher than that quantified with (NH4)2SO4. To reduce substrate inhibition in acetate medium, fed-batch and repeated-batch processes were evaluated using (NH4)2SO4 or yeast extract as nitrogen source. In the fed-batch process, the period of malate production was extended, and the maximum product concentration was increased to 11.49 ± 1.84 g/L with (NH4)2SO4 and 12.08 ± 1.25 g/L with yeast extract. In the repeated-batch process, the total acid production was highest within the first 240 h of fermentation, but optimization is required to maintain high production rates in later cycles. The lessons learned in this study will help in the development of further process strategies to maximize malate production using acetate as alternative substrate to the commonly used glucose.